2002
DOI: 10.1902/jop.2002.73.11.1377
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Periodontal Osseous Destruction and Remodeling: Principles and Implications for Diagnosis and Therapy

Abstract: Osteoclastic bone resorption is a prominent feature of periodontal disease. Bone resorption via osteoclasts and bone formation via osteoblasts are coupled, and their dysregulation is associated with numerous diseases of the skeletal system. Recent developments in the area of mediators of osteoclastic differentiation have expanded our knowledge of the process of resorption and set the stage for new diagnostic and therapeutic modalities to treat situations of localized bone loss as in periodontal disease. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 116 publications
(152 reference statements)
0
80
0
6
Order By: Relevance
“…IL-6 is also a potent stimulator of osteoclast differentiation and bone resorption (Gemmell et al, 1997;Hughes et al, 2006), which are typical of periodontitis. The intensity of IL-6 expression is positively correlated with attachment loss (Moreira et al, 2007) and IL-6 is associated with continuous tissue destruction in periodontitis (McCauley and Nohutcu, 2002). Furthermore, levels of IL-6 are elevated in periodontitis patients (Loos, 2005;Loos et al, 2000) and decreased after successful periodontal therapy (D'Aiuto et al, 2004a;2004b).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is also a potent stimulator of osteoclast differentiation and bone resorption (Gemmell et al, 1997;Hughes et al, 2006), which are typical of periodontitis. The intensity of IL-6 expression is positively correlated with attachment loss (Moreira et al, 2007) and IL-6 is associated with continuous tissue destruction in periodontitis (McCauley and Nohutcu, 2002). Furthermore, levels of IL-6 are elevated in periodontitis patients (Loos, 2005;Loos et al, 2000) and decreased after successful periodontal therapy (D'Aiuto et al, 2004a;2004b).…”
Section: Discussionmentioning
confidence: 99%
“…16 IL-6 has been associated with attachment loss and tissue destruction due to its effect on osteoclast differentiation. 17,18,19 In addition, IL-6 is regulated at the transcriptional level and a polymorphism in the region of -572 G/C plays a critical role in the regulation of transcription. 20,21 On the other hand, IL-10 is an anti-inflammatory cytokine that down-regulates the pro-inflammatory immune response of monocytes and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the well-accepted role of TLR4 in immune response (Takeda and Akira 2005), the participation of TLR4 in the regulation of the bone mineral content of mammals was also considered based on the observation that LPS provokes an osteolytic response yielding aggressive bone resorption (McCauley and Nohutcu 2002). More importantly, Johnson et al (2004) reported that mice harbouring a loss-of-function mutation in the TLR4 gene have a body architecture characterized by increased bone mineral content and density, higher resistance to fracture and a decreased body fat (up to 70% less body fat gain) compared to wild-type mice.…”
Section: Introductionmentioning
confidence: 99%